PERANCANGAN BRAND ACTIVATION KAMPUNG LUKIS JELEKONG BERSAMA GREEBEL DALAM MENIGKATKAN BRAND AWARENESS UNTUK USIA 13-18 DI BANDUNG - Orlinfelicia, Rinda; Syafikarani, Aisyi; Rangga Lawe, I Gusti Agung (eProceedings of Art & Design, 2024)
There has been no stability in tourists from within and outside the country since the restrictions were implemented. Promotion of the Jelekong Lukis Village through the event, namely Jelekong Fest, was less effective because it was accompanied by the celebration of National Puppet Day, so the only potential that was highlighted was the wayang. The methodology used in this research was qualitative by collecting observational data, literature studies, interviews and questionnaires. Based on the analysis that has been carried out in the promotional content of Kampung Lukis Jelekong's Instagram social media, the use of this social media is still not optimal. With less informative Instagram feeds and fonts that are not suitable for use. This causes a lack of enthusiasm from Instagram users. Based on the data collection and analysis that has been carried out, it can be concluded that Kampung Lukis Jelekong has good potential for tourism, but the lack of attention in the field of promotion and social media is a challenge for this tourist attraction. Therefore, Kampung Lukis Jelekong needs brand activation promotional media through events that can provide direct interaction from the promoter to the visitors who come. Keywords: tourism, promotional media, event.